Fault diagnosis and restoration strategy based on Voronoi diagram and resolving set - Xiao-ding WANG; Li XU; Shu-ming ZHOU; Hui LIN (Tongxin xuebao)
As a communication backbone,high fault tolerance was a significant property in communication of WSNs.A novel fault diagnosis and restoration strategy based on Voronoi diagram and resolving set was designed.This strategy effectively reduced the communication cost during the fault diagnosis and recovery process through introducing a resolving set based coordinate system.Theoretical analysis and simulation results validate the performance of the proposed strategy.